Renal dysfunction increases the risk of recurrent stroke in patients with acute ischemic stroke. (October 2018) - Wang, I-Kuan; Lien, Li-Ming; Lee, Jiunn-Tay; Liu, Chung-Hsiang; Chen, Chih-Hung; Lin, Ching-Huang; Jeng, Jiann-Shing; Hu, Chaur-Jong; Yen, Tzung-Hai; Chen, Sien-Tsong; Chiu, Hou-Chang; Tsai, I-Ju; et al.
Abstract: Background and aims: This study investigated risks of short-term (1 and 3 months) and long-term (1-year) recurrent stroke associated with glomerular filtration rate (eGFR) in patients with acute ischemic stroke. Methods: From the Taiwan Stroke Registry data, we identified 45, 876 acute ischemic stroke patients from April 2006 to April 2014 and classified them into 4 groups based on the eGFR at admission: ≥ 90, 60–89, 30–59, and <30 mL/min/1.73 m 2 or on dialysis. The risks of 1-month, 3-month and 1-year recurrent stroke related to the eGFR levels were investigated. Results: Both the risks of short-term and long-term recurrent stroke increased as the eGFR levels declined. The 1-month recurrent incidence rates increased steadily from 0.54 to 0.59, 0.84 and 0.89 per 1000 person-days, as the eGFR declined from ≥90 to 60–89, 30–59, and <30 mL/min/1.73 m 2 or on dialysis, respectively. Compared to patients with eGFR ≥90 mL/min/1.73 m 2, the adjusted subhazard ratio of 1-month recurrent stroke decreased from 1.69 (95% confidence interval (CI) = 1.24–2.31) for patients with eGFR < 30 mL/min/1.73 m 2 or on dialysis to 1.14 (95% CI = 0.91–1.43) for patients with eGFRs of 60–89 mL/min/1.73 m 2, considering the competing risk of deaths. Similar patterns were also observed for the adjusted HRs of 3-month and 1-year recurrent stroke, but with reduced hazard values, by the corresponding eGFR levels. Conclusions: There is an independent graded association between an increased risk of recurrent stroke and declining eGFR levels in patients with acute ischemic stroke. Highlights: This study investigated the recurrent stroke risks in ischemic stroke patients by the glomerular filtration rate (eGFR). The eGFR levels were classified to 4 categories: ≥90, 60–89, 30–59, and <30 mL/min/1.73 m 2 or on dialysis. There is an independent graded association between an increasing risk of recurrent stroke and the declining eGFR.